1985
DOI: 10.1016/0014-5793(85)80841-3
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration and characterization of α‐human atrial natriuretic factor in human plasma

Abstract: This paper describes a highly specific and sensitive radioimmunoassay for a-human atrial natriuretic factor (a-hANF), the C-terminal 28-amino-acid residue portion of human prepro-ANF in human plasma. A novel extraction and prepurification procedure allowed for detection of levels of immunoreactive-a-hANF as low as 0.5 fmol/ml. In normotensive subjects, levels in the range l-23 fmol/ml (mean = 8.9 fmol/ml) were found. Combined gel permeation and HPLC analysis demonstrated that this ir-a-hANF was comprised virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 16 publications
6
23
0
Order By: Relevance
“…The moab shows complete crossreactivity with rat ANP I, II, and III, rat ANP (1-28) and human ANP fragment (7-28) while there is no inhibition of 125I-ANP binding by rat ANP fragments (13-28), (18-28) and (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) (fig. 1).…”
Section: Properties Of the Lla-all Anti-oe-h-anp Moabmentioning
confidence: 99%
See 1 more Smart Citation
“…The moab shows complete crossreactivity with rat ANP I, II, and III, rat ANP (1-28) and human ANP fragment (7-28) while there is no inhibition of 125I-ANP binding by rat ANP fragments (13-28), (18-28) and (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) (fig. 1).…”
Section: Properties Of the Lla-all Anti-oe-h-anp Moabmentioning
confidence: 99%
“…The predominant lowMr species purified from human atrial is o~-human ANP (ot-h-ANP). So far there exists only indirect evidence as to whether this is the only circulating form of ANP [8][9][10][11]. Here, we describe the purification of atrial peptides from human plasma by immunoaffinity chromatography and reversedphase HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction procedures as well as characteristics of our highly sensitive and specific radioimmunoassay for determination of ANF in plasma have been previously described (6,9). Application of the extraction proce dure to aliquots of ascitic fluid yielded high recovery rates, not different from those obtained in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to ANF re lease stimulated by the hemodynamic changes following ascites infusion or due to elevated ANF concentrations in ascitic fluid. Whereas the presence of atrial natriuretic factor (ANF) has been demonstrated in various fluids of the human body, such as plasma (6), urine (7) and cerebrospinal fluid (8), ascitic fluid has not been examined as yet for the occurence of ANF.…”
mentioning
confidence: 99%
“…the prohormone is stored in secretory vesicles. ANF-126 is further processed enzymatically and secreted into the blood, where the biologically active C-terminal ANF-28 has been defined as the circulating hormone [27,35,36]. Increased dietary sodium intake has been shown to stimulate ANF release [37].…”
mentioning
confidence: 99%